Ireland : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Ireland entered the COVID pandemic with reduced vulnerabilities and high growth, especially in multinational enterprises (MNEs)-dominated sectors. The pandemic has had a highly asymmetric impact on the economy. The domestic sectors contracted by about 10 percent in 2020 and unemployment reached 30 percent at the peak of the first wave, while MNEs continued to grow strongly, driving overall GDP growth to 3.4 percent. A swift policy response has been effective in mitigating the crisis impact and protecting households and firms. The domestic sectors are expected to partially recover in 2021, with GDP growth projected at 4.6 percent. Downside risks stem from uncertainties surrounding new COVID variants, post-Brexit trade arrangements, and likely changes in international taxation.